The 1920 Antiquities Ordinance of Palestine and the date 1700 for Antiquities: New Discoveries - Ḳlẹter, Raz (Advances in ancient Biblical and Near Eastern research, 2022)
The Antiquities Ordinance (Law) of 1920 was instrumental for the archaeology of Palestine in the British Mandate period. It was highly successful in having significant influence, for many years, on the antiquities legislation of Jordan and Israel after 1948. This law has hardly been studied so far, except for one detail—the setting of the year 1700 CE for defining antiquities. Based on many as yet unpublished documents from several archives, I discuss in this article the complex origins of the 1920 Antiquities Law. Contrary to the current scholarly consensus, it was created by many agents (historians, archaeologists, legal experts, politicians, military men), working since 1918 in Egypt, Palestine, Britain, and the international peace conferences held after World War I. The law was a compromise between the desire to facilitate the excavation, trade, and export of finds (for the benefit of Western institutions) and the wish to protect sites and keep finds in Palestine (for the benefit of local populations). The year 1700 CE was not a measure taken against protecting the area’s (late) Ottoman heritage, but a reasonable choice at a time when the discipline of historical archaeology did not exist yet.